Data and code related to the publication "Recovering membrane interaction kinetics of single molecules from 3D tracking data" by Lundin et al. - Lundin, Erik; Volkov, Ivan; Johansson, Magnus (Uppsala University, 2026)
This repository contains analysis code related to the manuscript "Recovering membrane interaction kinetics of single molecules from 3D tracking data" by Lundin et al. (2026) Biophysical Journal

Abstract

Interactions between cytosolic biomolecules and the bacterial inner membrane are fundamental to many cellular processes, yet directly measuring their binding kinetics in living cells remains challenging. Conventional two‑dimensional single‑molecule tracking analyses can be insufficient, particularly when membrane association does not markedly alter the diffusion rate. Here, we present a method to recover membrane interaction kinetics from three‑dimensional single‑molecule trajectories in rod-shaped bacteria. Using simulated 3D tracking data, we identify membrane‑associated motion by quantifying how well short trajectory segments follow the circular curvature of the cell membrane. The resulting measure is further analyzed using a hidden Markov modeling framework, enabling robust discrimination between cytosolic and membrane‑bound states and capturing the dynamics of state transitions without requiring diffusion‑rate changes or direct colocalization with membrane markers. This work establishes a general framework for extracting membrane interaction kinetics from 3D single‑molecule tracking data in live bacteria, and highlights the value of realistic microscopy simulations for quantitative interpretation and systematic bias assessment.

A detailed list of files and file organizations can be found in the readme file.
Keywords: Biochemistry and cell biology not elsewhere classified; Bioinformatics and computational biology not elsewhere classified; Medical and Health Sciences; Medicin och hälsovetenskap; Bioinformatics (Computational Biology); Bioinformatik (beräkningsbiologi); Biochemistry; Biokemi